Join the current - Huam, Wen Yuan (2016)
This report presents Join The Current - an educational literacy campaign set against the global and local decline of news consumption amongst youths. Pioneered by four final-year students from the Wee Kim Wee School of Communication and Information, the campaign aims to use current affairs and information literacy as tools to inform, engage and equip preadolescents for their transition into active citizens.